2011
DOI: 10.4028/www.scientific.net/amr.250-253.994
|View full text |Cite
|
Sign up to set email alerts
|

Experiment Research on Basic Mechanic Property of Recycled Concrete with Different Ratio of Recycled Aggregate

Abstract: The test confects C20, C25, C30, C35 and C40 recycled aggregate concrete, and the percentage of recycled aggregate are 0%, 20%, 30%, 50%, 70% and 100%,the test age of sample are 7d,28d and 56d.Through test, the cube crushing strength,prismatical compressive strength and elasticity modulus of recycled aggregate concrete with different recycled aggregate percentage and different ages are studied, and compare with general concrete. Test show that, with the development of age, the strength development law of recyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Guo et al studied the compressive properties of concrete blocks containing recycled aggregate of concrete and they found that the compressive properties of RAC blocks were similar to those of ordinary concrete after incorporating recycled aggregates [18]. Sun and Xiao studied the strength and elastic modulus of RAC at different recycled aggregate dosages and ages of concrete, they found that the strength developing rule of RAC was similar to that of ordinary concrete with age growing, and the strength and modulus of elasticity for RAC decreased with the increase of recycled aggregate dosage [19]. Tabsh and Abdelfatah believed that the compressive strength and splitting tensile strength of RAC depended on the mixing ratio [20].…”
Section: State Of the Artmentioning
confidence: 99%
“…Guo et al studied the compressive properties of concrete blocks containing recycled aggregate of concrete and they found that the compressive properties of RAC blocks were similar to those of ordinary concrete after incorporating recycled aggregates [18]. Sun and Xiao studied the strength and elastic modulus of RAC at different recycled aggregate dosages and ages of concrete, they found that the strength developing rule of RAC was similar to that of ordinary concrete with age growing, and the strength and modulus of elasticity for RAC decreased with the increase of recycled aggregate dosage [19]. Tabsh and Abdelfatah believed that the compressive strength and splitting tensile strength of RAC depended on the mixing ratio [20].…”
Section: State Of the Artmentioning
confidence: 99%
“…Sun et al studied the compressive strength and elastic modulus of RAC at different replacement ratios and ages and found that with the development of age, the strength development law of RAC is similar to that of general concrete. With the increase of the replacement ratio of recycled aggregate, the strength and elastic modulus of recycled aggregate concrete show the trend of decline [17]. Tabsh et al carried out tests of mechanical properties with recycled coarse aggregate source and target concrete strength as variable parameters.…”
Section: State Of the Artmentioning
confidence: 99%
“…The so-called recycled concrete, is to make the waste concrete block crushed, washed, graded, respectively, to form recycled coarse aggregate and fine aggregate, which can be used as aggregate in concrete [1]. A lot of achievements on the physical and mechanical properties of recycled concrete have been made at home and abroad [2][3][4]. In order to use the recycled concrete in structural engineering, more and more studies on RAC members, structural mechanical properties and hysteretic behavior have been made recently [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%